From Profit to Purpose: Reimagining Corporate Social Responsibility as a Catalyst for Achieving the SDGs in Local Communities - Siham El-Kafafi (Journal of Sustainable Community Development (JSCD), 2025)
Corporate Social Responsibility (CSR) is undergoing a transformative shift fromperipheral philanthropy to a central pillar of sustainable business strategy, particularly inrelation to achieving the United Nations Sustainable Development Goals (SDGs). Thispaper critically examines the evolving role of CSR in driving sustainable and inclusivecommunity development. Drawing on a comprehensive literature review and illustrativecase studies—both global and from New Zealand—the research explores how businessesare embedding CSR practices within their strategic frameworks to address pressing socialand environmental challenges. It analyzes innovative CSR models, stakeholderengagement approaches, and the measurable impacts of these initiatives on localcommunities.Key findings reveal that organizations aligning CSR with their core values and the SDGsdemonstrate stronger outcomes in environmental stewardship, social cohesion, andcommunity trust. The study concludes with forward-looking recommendations forcorporate leaders, policymakers, and civil society actors to enhance the effectiveness,transparency, and scalability of CSR in delivering meaningful and lasting change.